Optimasi Hasil Belajar Matematika Kelas 3 dengan Metode Diskusi di SDN 036 Inpres Bonde Kecamatan Campalagian - A.M., Muh. Inayah; Arifin, Iqbal (Celebes Journal of Elementary Education, 2025)
Student learning outcomes in the field o Student learning outcomes in the field of mathematics subject matter: the idea of ​​carrying out combined or mixed calculations using the discussion method for grade 3 students at SDN 036 Inpres Bonde. The research activity method carried out was using Classroom Action Research (PTK) which was carried out in several cycles, where each cycle consisted of two meetings. The results of the research prove that the discussion method can improve student learning outcomes in mixed arithmetic operations material in class 3 of SDN 036 Inpres Bonde. which was analyzed using quantitative descriptive. In the pre-cycle activities of 28 students, there were only 8 students who completed the KKM with a class success percentage of 28.57%. The results of learning improvements in cycle 1 increased by 17.86% where there were 13 students who completed the KKM with a class success percentage of 46.43%. After cycle 2 there was a significant increase in learning outcomes of 42.86% compared to cycle 1, where 25 students completed the KKM with a class success percentage of 89.29 01. Teacher activity increased. Based on the results of this research, it can be concluded that the results of learning mathematics regarding mixed arithmetic operations using the discussion method for class 3 students at SDN 036 Inpres Bondehave increased and are acceptable.athematics subject matter: the idea of ​​carrying out